Analisis SWOT sebagai dasar perumusan strategi digital dan diversifikasi bisnis PT Pegadaian (Persero) dalam meningkatkan keunggulan kompetitif di era transformasi keuangan - Octavia, Irene Hevy (Maliki Interdisciplinary Journal, 2025)
This study analyzes the application of SWOT analysis as a basis for formulating PT Pegadaian (Persero)'s business strategy amidst the competition in the modern financial industry. The study focuses on the implementation of digital strategies and business diversification through Pegadaian Digital Service (PDS) as an innovation to strengthen the company's competitiveness and resilience. This study uses a library research method with reference to various scientific journals and relevant previous research. The analysis results show that Pegadaian has key strengths in digital innovation, brand reputation, and government support, but still faces weaknesses such as system limitations and customer digital literacy. Opportunities arise from increased financial inclusion and technological modernization, while threats come from the emergence of fintech and cybersecurity risks. Based on the results of the SWOT matrix, four main alternative strategies were obtained (SO, ST, WO, and WT) that can be used as a basis for strengthening Pegadaian's business strategy to achieve sustainable competitive advantage.